Vertex Algebroids over Veronese Rings - Malikov, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We find a canonical quantization of Courant algebroids over Veronese rings. Part of our approach allows a semi-infinite cohomology interpretation, and the latter can be used to define sheaves of chiral differential operators on some homogeneous spaces including the space of pure spinors punctured at a point.